Case Report: Left ventricular apical hypertrophy in a patient with Leopard syndrome mimicking a cardiac tumor: a diagnostic challenge resolved by multimodality imaging - Liu, Hui; Zheng, Yue; Huo, Huaibi; Peng, Xin; Yang, Jun; Ma, Chunyan; Liu, Ting (Frontiers in Cardiovascular Medicine, 2024)
Abstract Background: LEOPARD syndrome (LS) is a rare genetic disorder presenting various clinical manifestations from childhood, complicating its diagnosis. We aim to refine the imaging presentation of LS and emphasize the importance of multimodality imaging in enhancing diagnostic accuracy and preventing serious cardiovascular events. Case: A 41-year-old woman was admitted to the hospital with a suspected apical tumor detected by transthoracic echocardiogram (TTE), which was later identified as apical myocardial hypertrophy through cardiac magnetic resonance imaging (CMR). She had abnormal electrocardiograms from the age of 2 years and freckles around the age of 4 years. In recent years, she has experienced exertional dyspnea. Supplemental coronary computer tomography angiography (CCTA) revealed diffuse coronary dilatation. The integration of multimodality imaging and clinical manifestations led to a suspicion of LS, which was confirmed by subsequent genetic testing. The patient declined further treatment. A three-month follow-up CMR showed no significant change in the lesion. Conclusion: This report elucidates the diagnostic transition from an initial suspicion of an apical tumor by TTE to a definitive diagnosis of left ventricular apical hypertrophy by CMR in a 41-year-old female with LS. It underscores the value of multimodality imaging (TTE, CCTA, CMR) in unraveling unusual cardiac manifestations in rare genetic disorders such as LS.